Concerns Related to the Consequences of Pediatric Cannabis Use: A 360-Degree View - Flavia Padoan; Chiara Colombrino; Francesca Sciorio; Giorgio Piacentini; Rossella Gaudino; Angelo Pietrobelli; Luca Pecoraro (MDPI AG, 2023)
Cannabis, a plant known for its recreational use, has gained global attention due to its widespread use and addiction potential. Derived from the Cannabis sativa plant, it contains a rich array of phytochemicals concentrated in resin-rich trichomes. The main cannabinoids, delta-9-tetrahydrocannabinol (THC) and cannabidiol (CBD), interact with CB1 and CB2 receptors, influencing various physiological processes. Particularly concerning is its prevalence among adolescents, often driven by the need for social connection and anxiety alleviation. This paper provides a comprehensive overview of cannabis use, its effects, and potential health risks, especially in adolescent consumption. It covers short-term and long-term effects on different body systems and mental health and highlights the need for informed decision making and public health initiatives, particularly regarding adolescent cannabis use.